Elaboración de un modelo de gestión para el desarrollo turístico del cantón La Maná, Provincia de Cotopaxi 2018 - Toala Tuárez, Patricio Javier (2018)
The general objective of this research was to create a management model for the La Mana canton tourist development due to the great potential, supply and demand that it account, the research is descriptive-exploratory with a qualitative approach for which three objectives are proposed. The first is aimed at carrying out the situational diagnosis and inventory of the tourist attractions of the La Maná, the district economic activity, degree of studies, the infrastructure like a state roads and tourist facilities that canton possesses, tied to updating tourist inventories of ten attractions with a growing tourist demand. The second objective a market study was developed to identify the applicability of the management model in the canton La Maná to inhabitants of La Maná, Quevedo, Valencia and Buena Fe, taking these cantons as the main market due to their proximity. The survey was made up of 15 questions which refer to residence place, age, sex, predisposition of expenses in a trip, the way they make their trip, tourist attractions known or visited, among others. The last three questions do reference to applicability of management model as a Project to canton tourist development. For the third objective It is proposed to design a tourism management model which has a summary, tourism services lines, regulatory framework, strategic direction, mission, vision, strategic objectives, values, organizational structure, matrix of stakeholders, which will allow us to identify the needs and capacities of canton, in the same way was done a SWOT analysis which allowed us to identify internal and external aspects of canton. Finally, was done a zoning of management model that will serve as a tool for a better administration of tourist resources La Mana canton.